Research on the Layout of Courtyard Space in Underground Commercial Streets - Yu He; Xiaowei Chen; Meixuan Tian; Chi Zhang; Jing Kang (Buildings)
Underground pedestrian streets play a crucial role in urban spatial systems, yet the positioning of atrium spaces in existing underground walkways is often determined empirically without adequate consideration of spatial rationality in relation to public environmental behavior. Properly designed atrium spaces can significantly enhance spatial quality and pedestrian experience, effectively revitalizing underground environments. This research investigates the rationality of atrium spatial distribution in underground pedestrian streets, with particular emphasis on developing an evaluation framework for assessing atrium layout appropriateness, using pedestrian congregation patterns shaped by spatial network morphology as the primary evaluation criterion. Through comprehensive field observations and computational simulations, the study examines the interaction between existing underground street network configurations and pedestrian behavior, pioneering the application of spatial design network analysis (sDNA) technology to optimize atrium spatial positioning strategies, thereby establishing a more scientific methodology for atrium layout planning. The proposed approach was validated through a case study of Longhu Underground Pedestrian Street in Handan, ultimately providing a systematic method for verifying atrium distribution rationality. The research establishes an innovative framework that integrates computational analysis into underground spatial planning, incorporates pedestrian flow prediction into architectural design processes, and embeds performance-based evaluation into urban renewal initiatives. Findings demonstrate that sDNA technology can accurately predict pedestrian congregation patterns across various underground street configurations, providing a data-driven foundation for assessing atrium location rationality and supporting the optimization of existing underground spaces. These outcomes are expected to offer valuable scientific references for the design and improvement of atrium spatial distribution in future underground pedestrian systems.